Interleukin-5 modulates interleukin-8 secretion in eosinophilic inflammation - L. H. Faccioli; A. I. Medeiros; A. Malheiro; R. C. L. R. Pietro; A. Januário; B. B. Vargaftig (Hindawi Limited, 1998)
Serum and BALF (bronchoalveolar lavage fluid) IL-8 levels and serum levels were investigated in Tox ocara canis infected guinea-pigs and the role of IL-5 as a modulator of cytokine secretion was studied. Serum levels increased early in infected animals, exceeding control levels 4 h after infection, peaked between days 6 and 18, and continued to exceed control levels after 48 days of infection. Serum and BALF IL-8 levels showed the same profile as blood eosinophilia, increasing 6 days post-infection and peaking between days 18 and 24. Treatment of infected animals with anti-IL-5 Ab suppressed eosinophilia with a parallel increase in blood IL-8 levels, whereas no change was found in levels. To support our in vivo observation we carried out experiments in vitro using guinea-pig LPS-stimulated adherent peritoneal cells which release large amounts of IL-8 into the supernatants. When rIL-5 was added to LPS-stimulated cells, 65% inhibition of IL-8 release into the supernatants was observed. Pre-incubation of cells with anti-IL-5 Ab prevented the inhibition of IL-8 release into the supernatants induced by rIL-5. Our results demonstrate for the first time that TNF- α and IL-8 are released concomitant with or after IL-5 in the eosinophilic inflammation induced by T. canis . Moreover, in addition to showing that IL-5 is fundamental for the induction of blood eosinophilia, the present results suggest that this cytokine may play a new biological role by acting as modulator of IL-8 secretion.